Determination of coagulation factors activity in patients with II stage hypertension in combination with COPD using highly specific tests containing snake venom - Самойлова, Світлана Олегівна; Плєнова, Ольга Миколаївна (ScienceRise: Medical Science, 2016)
The aim of research was to determine characteristics of plasma hemostasis changes using highly specific snake venoms in patients with HT in combination with COPD. Methods. Special laboratory tests were used: ancystron test containing snake of Agkistrodon (Copperhead) genus venom, lebetox-test containing Vipera lebetina (Blunt-nosed viper) venom, and echitox test containing Echis multisquamatus (Multiscale saw-scaled viper) venom. Results. As a result of research, the activation of hemocoagulation on the X-factor coagulation level in patients with II stage HT, thrombin and fibrin formation intensification in patients with II-III stage COPD, and misbalance in the blood coagulation system, which demonstrates a hypocoagulation tendency, combined with a strong activation of the coagulation final phase at HT and COPD comorbid course were found